EFECTO DE LAS AVES SOBRE LA GERMINACIÃ“N DE COTONEASTER FRANCHETTI BOIS (ROSACEAE) - Dellafiore, Claudia Marisel; Rosa, MarÃa José (European Scientific Journal, ESJ, 2015)
Invasive plants change the structure and species composition of community invaded and create microhabitats that modify their abiotic characteristics. Cotoneaster genus includes ninety species distributed in temperate regions of Europe, North Africa and most of Asia. Several species have been introduced in many countries as ornamental and in some of them have become invasive weeds. Cotoneaster franchetti has invaded native forests in the province of Cordoba - Argentina and birds have been considered responsible for its spread. However, the fact that birds disperse seeds does not necessarily imply an effective dispersion because passage through digestive tract can adversely affect germination. The aim of this study was to determine if the seeds of C. franchetti suffer damage when passes through bird’s digestive tract and if this process affects their viability and germination. Germination power, initiation and rate germination was compared between seed from fruits and feces bird. Viability test of tetrazollium was performed at the end of the experience. According the results, the germination power was significantly lower for seeds passed through the bird’s digestive tract than the fruits. Seeds ingested by birds showed an earlier onset of germination and a higher germination rate, this would benefit to C. franchetti because they decrease the risk of mortality from predation or burial and would favour fast seedling establishment